Towards poor-centred value chain for sustainable development: a conceptual framework - Minh, Thai Thi; Osei-Amponsah, Charity (Wiley, 2021)
Value chain for development (VCD) has increasingly been promoted for poverty reduction; yet, there is inadequate evidence on its effectiveness. Based on a comprehensive literature review, this article offers reasons why evidence on VCD impacts on poverty reduction is uncertain. It also suggests a conceptual framework for the poor-centred value chain for sustainable development to guide a better analysis of VCD participation and poverty impacts. The framework is particularly useful for researchers involved in research for development related projects in the VCD space. As it provides an analytical lens to understand the broader contextual situation of the poor, co-design solutions with multi-stakeholders and implement appropriate “fit-toneeds” strategies that ensure the poor benefits from their VCD participation. The article contributes to the existing VCD discourse by reflecting on the multidimensional nature and dynamism of poverty reduction, the poor's heterogeneity and their value chain readiness and VCD impacts on poverty.